Results of trawl counts for juvenile pink salmon in the Bering and Okhotsk Seas in 2024 and prospects for the returns and catch in the Karaginsky subzone and Okhotsk Sea in 2025 - A. A. Somov; E. A. Shevlyakov; A. N. Starovoitov; V. A. Shevlyakov; I. V. Melnikov (Известия ТИНРО)
The key stage of juvenile pink salmon monitoring is the survey of their fall feeding in the sea that detects the year-class strength. The results of this survey are used for forecasting of the pink salmon returns to the Karaginsky fishing subzone in Bering Sea and to the Okhotsk Sea and the landing in the next year. The trawl surveys with two research vessels have conducted in recent years that allows to cover vast areas in a short time and to exclude repeated counts of the same fish on neighbor transects. In 2024, such trawl survey for pink salmon counting was conducted in the western Bering Sea and Okhotsk Sea that provided representative data on the juveniles abundance used for forecasting their returns and catches in the Karaginsky fishing subzone and Okhotsk Sea. The abundance of pink salmon in the western Bering Sea was estimated in 452∙106 ind. that was about a half of their numbers in previous even years (2018, 2020, 2022). Their return to the Karaginsky fishing subzone in the next year is expected as 72∙106 ind. at the lower limit of confidence interval, that provides the catch of 49∙103 t with the expected weight of spawners about 1 kg and 32 % escapement to the spawning grounds. In the Okhotsk Sea, the abundance of pink salmon was estimated in 1077∙106 ind. that was lower than in 2020 and 2022. Their expected return to the Okhotsk Sea in the next year is expected as 123∙106 ind. at the lower limit of confidence interval, that provides the catch of 100∙103 t with the weight of 1.3 kg and escapement of 35 %. Abundance in «northern» and «southern» regional complexes of local stocks is estimated for pink salmon in the Okhotsk Sea using cluster analysis with the expectation-maximization algorithm (EM clustering); the «northern» group prevailed with the ratio 64:36 %.